THE RELATIONSHIP BETWEEN SOCIAL MEDIA AS A SOCIAL SPACE AND TRAVEL DECISION MAKING OF GENERATION Z IN BENGKULU CITY - Aditya Eka Satrio; Panji Suminar; Ika Pasca Himawati (SOSIOEDUKASI, 2026)
Social media has evolved into a digital social space that enables Generation Z to interact, construct identities, and exchange meanings through visual content and online communication. This study aims to analyze the relationship between social media as a social space and the travel decision-making of Generation Z in Bengkulu City. The research employed a quantitative method with a correlational approach, involving 384 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, classical assumption tests, linearity testing, and Pearson correlation. The findings indicate a positive tendency in how Generation Z utilizes social media as a social space, as well as in their travel decision-making processes. The Pearson correlation test produced a coefficient of r = 0.792 with p = 0.000, demonstrating a positive and significant relationship between the two variables. This implies that the greater the involvement and interaction experienced through social media, the stronger the tendency of Generation Z to form interest, preferences, and actual decisions to visit tourist destinations. These results confirm that social media functions not only as an informational medium but also as a dynamic arena of social interaction that shapes travel decisions through digital communication and information exchange within online communities.